The Fairwork Foundation: Strategies for improving platform work in a global context. Issue 112 (June 2020) - Graham, Mark; Woodcock, Jamie; Heeks, Richard; Mungai, Paul; Van Belle, Jean-Paul; du Toit, Darcy; Fredman, Sandra; Osiki, Abigail; van der Spuy, Anri; Silberman, Six M.
Abstract: This paper introduces the Fairwork Foundation, a research initiative that is also developing an intervention around the quality of work on digital labour platforms. Lacking the ability to collectively bargain, many platform workers have little ability to negotiate wages or working conditions with their employers. As a result of this new, digitally-managed market for work, many workers have jobs characterised by long and irregular hours, low income, and high stress. Fairwork's field research across India and South Africa finds challenges for workers across a range of issues which form the basis for a set of decent work principles on: pay, conditions, contracts, management, and representation. The results of the field research are being used to rank and compare platforms against these principles as a means to encourage decent, and discourage 'un-decent' platform work.